Front Cover: Label‐Free Phase Change Detection of Lipid Bilayers Using Nanoscale Diamond Magnetometry (Adv. Quantum Technol. 4/2021). Issue 4 (3rd April 2021) - Ishiwata, Hitoshi; Watanabe, Hiroshi C.; Hanashima, Shinya; Iwasaki, Takayuki; Hatano, Mutsuko
Abstract : The diffusion constant of a lipid bilayer, a biological parameter that determines the dynamics of the lipid bilayer, was determined by making use of the extremely small detection volume offered by nanoscale nuclear magnetic resonance (NMR) using nitrogen vacancy (NV) center in diamond. Observation of the diffusion constant at different temperature reveals different phases of the lipid bilayer. The result builds a foundation for label‐free imaging of cell membranes for the observation of phase composition and pristine dynamics that determine cellular functions. For further details see article number 2000106 by Hitoshi Ishiwata and co‐workers.